INTERPRETASI MAHKAMAH KONSTITUSI TERHADAP PENGUJIAN PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG - Hafidzi, Anwar; Sugesti, Panji (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2019)
Abstract: The Constitutional Court of the Republic of Indonesia has 4 (four) authorities and one obligation, as for those authorities, namely: (1) The Constitutional Court has the authority to adjudicate at the first and last level whose decisions are final to test the Law against the Constitution, (2) decide authority disputes of State Institutions whose authority is granted by the Constitution, (3) decide upon the dissolution of political parties, (4) and decide upon disputes about the results of general elections. The obligations, namely the Constitutional Court is obliged to give a decision on the opinion of the House of Representatives regarding the alleged violation by the President and / or Vice President. Beyond the specified authority, the Constitutional Court has increased its authority to test the Substitute Government Regulations. The research method used in this study is a type of normative legal research that is a literature study or documentary, by examining theories, concepts and legal principles. The results of this study found that there is indeed no rule that gives the Constitutional Court authority to test regulation in lie of law, but the Constitutional Court has the consideration that the legal norms contained in the Perppu are the same as the Law. The results of this study are that the interpretation used by constitutional justices to test Perppu is a teleological and sociological interpretation.Keywords: Interpretation; Test; PERPPU; Constitutional Court.